Evaluation of dental internship clinical care before and during the COVID-19 pandemic (Research, Society and Development, 2024)
The dental internship allows the student to develop and evaluate their acquired knowledge, through the practical demonstration of motor skills, dexterity and aptitude for working in the oral environment. The objective of this study was to evaluate the dental internship at the State University of Amazonas through qualitative and quantitative analysis of the procedures performed and to evaluate the impact that the COVID-19 pandemic had on it. Quantitative data on care and qualitative evaluation of procedures from the dentistry internship of the 9th period of graduation were collected, being carried out in two periods before the COVID-19 pandemic and two periods during the pandemic. The data underwent descriptive and statistical analysis, using the Kruskal-Wallis test, and if there was a statistical difference (p